Phonetic Spelling Algorithm Implementations for R - Howard, II, James P. (Journal of Statistical Software, 2020)
The phonics package provides several functions for indexing words by their English language pronunciation. Over nearly one hundred years, many different algorithms have been developed to support word and name indexing. From Soundex, developed in the early 20th century and predating the digital computer, through to modern digital phonetic algorithms like Phonex, the phonics package provides support for more than a dozen methods. Together, these provide phonetic algorithms appropriate for use in name indexing and name matching across a variety of English language use cases.